Collaborative Urban Governance Model in Environmental Management of Industrial Area - Tri Sulistyaningsih; Mohammad Jafar Loilatu; Saiman Saiman; Nofianda Fatimah Azzahra; Nanda Adityawan (Journal of Government and Civil Society, 2021)
This paper's purpose for this study is to provide an overview related to the partnership or the cooperation between the government and the private sector, specifically the manager of the industry and the community in the environmental management of the industrial area in Gresik and Sidoarjo Regency. This research used a qualitative approach to analyze the data, interviews, documentation, and questionnaires. This study revealed that the environment's management in a sustainable manner should be supported by stakeholders, the government, the community, and the private sectors. Also, this research attends to instill a sense of environmental concern in the entire party. Collaborative urban governance sustainabilitycan not be separated from the leader's success in embracing the related parties and using existing industry resources. The stakeholder determines the success of managing the industrial area in the Gresik and Sidoarjo Regency, government, public, and private parties through a Collaborative Urban Governance model.Tujuan penelitian ini adalah untuk memberikan gambaran kemitraan atau kerjasama antara pemerintah dengan pihak swasta, khususnya pengelola industri dan masyarakat dalam pengelolaan lingkungan kawasan industri di Kabupaten Gresik dan Sidoarjo. Penelitian ini menggunakan pendekatan kualitatif untuk menganalisis data, wawancara, dokumentasi, dan angket. Studi ini mengungkapkan bahwa pengelolaan lingkungan secara berkelanjutan harus didukung oleh pemangku kepentingan, pemerintah, masyarakat, dan pihak swasta. Selain itu, penelitian ini hadir untuk menanamkan rasa kepedulian lingkungan pada seluruh pihak. Keberlanjutan Collaborative Urban Governance tidak lepas dari keberhasilan pimpinan dalam merangkul pihak terkait dan menggunakan sumber daya industri yang ada. Keberhasilan pengelolaan kawasan industri di Kabupaten Gresik dan Sidoarjo ditentukan oleh keterlibatan pemangku kepentingan, pemerintah, publik, dan swasta melalui model Collaborative Urban Governance.